Falling into Culturist Trap: Practice of Othering in An Indonesian English Language Classroom - Hidayati, Arini Nurul (Universitas Muhammadiyah Surakarta, 2018)
This paper illustrates my own teaching experience perceiving Kartini, my âCentral Javaâ student, who has different background of culture in the class. How I noticed her is part of impact on how my English teachers used to notice me. This is due to a belief that the capability of teachers to âoverlook the significance of their past experienceâ is one of the elements in shaping their present and future attitude in teaching and learning (Jalongo and Isenberg, 1995). Therefore, a narrative analysis which investigates nonnarative data through narration (Bamberg, 2012; Benson, 2014) Â is presented to illustrate the concept of the major hindrance in communication in the way of overgeneralizing, stereotyping, and reducing the students with something different or less than they are under the four constituents; stereotype, prejudice, culturalism, and essentialism (Holliday, 2010). The data inform that I once viewed my student in terms of difference from myself. Thus, I was misled by my own preconceptions and have fallen into the trap of Othering.